From Giant H ii regions and H ii galaxies to globular clusters and compact dwarf ellipticals. Issue 1 (24th August 2018) - Terlevich, Elena; Fernández-Arenas, David; Terlevich, Roberto; Gieles, Mark; Chávez, Ricardo; González-Morán, Ana Luisa
ABSTRACT: Massive star-forming regions like Giant H ii Regions (GHIIR) and H ii Galaxies (HIIG) are emission line systems ionized by compact young massive star clusters (YMC) with masses ranging from 10 4  M⊙ to 10 8  M⊙ . We model the photometric and dynamical evolution over a Hubble time of the massive gravitationally bound systems that populate the tight relation between absolute blue magnitude and velocity dispersion ( M B  − σ) of GHIIR and HIIG and compare the resulting relation with that one of old stellar systems: globular clusters, elliptical galaxies, and bulges of spirals. After 12 Gyr of evolution their position on the σ versus MB plane coincides – depending on the initial mass – either with the globular clusters for systems with initial mass M < 10 6  M⊙ or with a continuation of the ellipticals, bulges of spirals, and ultracompact dwarfs for YMC with M > 10 6  M⊙ . The slope change in the M B  − σ and M B -size relations at cluster masses around 10 6  M⊙ is due to the larger impact of the dynamical evolution on the lower mass clusters. We interpret our result as an indication that the YMC that ionize GHIIR and HIIG can evolve to form globular clusters and ultracompact dwarf ellipticals in about 12 Gyr so that present day globular clusters and ultracompact dwarf ellipticals may have formed in conditions similar to those observed in today GHIIR and HIIG.